System understanding and stakeholder analyses for the vulnerability of small‐scale agricultural producers in the Awash River basin, Ethiopia - Wolde Mekuria; Wondye Admasu; Shawl Abebe; Dagmawie Negash; Tefera Getachew; Abdulkarim Hussein Seid; Amare Haileslassie (People and Nature)
Abstract As climate change impacts intensify, water‐related problems and the vulnerability of small‐scale agricultural producers are expected to increase, suggesting the need for an inclusive and integrated management of water resources. This requires understanding the system and mapping the stakeholders, among other things. This study was conducted in the Borkena and Mille catchments of the Awash River basin, Ethiopia. It aimed to improve the understanding of how to improve the effectiveness of agricultural water management practices and water resource planning to address the vulnerability of small‐scale agricultural producers and draw implications for future stakeholder participation. Data were collected through key informant interviews, focus group discussions, literature reviews, and observation. The Driver‐Pressure‐State‐Impact‐Response framework was used to assess the system's state and its implications for the vulnerability of small‐scale agricultural producers. Stakeholder analyses involved mapping the stakeholders, examining their power and power resources, and evaluating their interest, influence, participation, trust levels, and dynamics of exclusion and empowerment. The results suggested that the natural and agricultural systems in both catchments are degrading, though multiple responses are implemented regarding agricultural water management practices. Diverse groups of stakeholders, such as development organizations, academic and research organizations, local administrative bodies, subregional policy and decision‐makers, communities and community‐based organizations, civil society organizations, donors, and nongovernmental organizations, participate in the planning, design, and implementation of agricultural water management practices. The stakeholder indicated multiple strategies such as promoting community participation and participatory decision‐making, aligning plans with communities' priorities and interests, improving collaboration and integration, improving access to resources, providing targeted capacity building and continuous awareness raising, and improving the implementation of policies and strategies to improve the effectiveness of interventions and address the vulnerability of small‐scale agricultural producers. Stakeholders have perceived strong legitimacy, but most of them have very little or no access and control over resources and connections with other stakeholder groups. Furthermore, stakeholders showed similarities in strategic options, differences in degree of influence, and demonstrated moderate to considerable trust in others. The alliance or relationship of most stakeholder groups in terms of coordinated action and coproduction using common resources was found to be weak, and most of the stakeholders lack competencies (that is, basic skills to plan, design, and implement interventions). We argue that a relatively weak relationship or alliance in terms of coordinated action and co‐production with common resources could affect the successful implementation of interventions. However, there is a high potential for collaboration, as most stakeholders did not vary in their strategic options. Furthermore, interventions related to agricultural water management practices could be implemented with low transaction costs, as the level of trust between the different stakeholders ranged from moderate to considerable. Read the free Plain Language Summary for this article on the Journal blog.